High levels of recruitment underline the sustainability of octocoral populations to harvest - Castro-Sanguino, Carolina; Lasker, Howard R. (Coral reefs, 2025)
Climate change is reshaping marine ecosystems. In recent decades, octocorals have become dominant on many Caribbean reefs as scleractinian corals diminish due to rising ocean temperatures. Octocorals are now vital for maintaining habitat complexity and supporting biodiversity, but some species have also been subject to harvesting. Thus, it is important to assess the impacts of their harvesting to reduce the risk of further destabilizing reef ecosystems. Here, we built a mechanistic individual-based model of Antillogorgia elisabethae population dynamics to evaluate the demographic consequences of long-term harvesting in The Bahamas. Our model explores different levels of recruitment, providing insights into the likely mechanisms by which populations are maintained, and evaluates whether the current harvest approach is sustainable and allows population recovery. We found that high levels of local recruitment were needed yearly to sustain repetitive harvests and avoid overexploitation. Demographic and harvest yield dynamics suggested that unregulated fisheries may lead to population collapse in the long term. Importantly, compensatory growth after harvest is key for population recovery. Knowledge of the early-life dynamics of these octocorals is limited. Yet, we demonstrate that by incorporating demographic dynamics into fishing assessments we can better inform fishing regulations to minimize ecological damage and support the long-term viability of their fisheries.